Bridging Artificial Intelligence Literacy and Technology Acceptance Among Elementary School Teachers: Evidence from a Structural Equation Model - Hamdan Husein Batubara; Mahfudz Siddiq; Amalia Risfianti; Amelinda Saharani (Al Ibtida: Jurnal Pendidikan Guru MI, 2025)
AbstractThis study investigates the correlation between artificial intelligence (AI) literacy and acceptance among Indonesian elementary school teachers using a structural equation model. A cross-sectional survey of 409 teachers indicated elevated AI acceptance and literacy levels. AI literacy strongly predicted acceptance and vice versa, suggesting a bidirectional relationship between these two variables. Demographic factors exerted minimal influence, whereas the frequency of AI use showed a moderate correlation between the two constructs. The structural equation model revealed that social influence, facilitating conditions, and the progressive development of AI competencies significantly influenced teachers' behavioral intentions and ethical awareness. These findings underscore the necessity of comprehensive, experiential professional development programs that promote deep, reflective, and ethical engagement with AI technologies. This study advocates for a systemic, culturally responsive approach to AI integration in elementary education, aligning training, infrastructure, collaborative culture, and personalized support to prepare teachers for effective and responsible AI utilization.Keywords: artificial intelligence, AI literacy, UTAUT, teacher acceptance, elementary education. AbstrakPenelitian ini menyelidiki korelasi antara literasi dan penerimaan kecerdasan buatan (artificial intelligence/AI) di kalangan guru sekolah dasar di Indonesia dengan menggunakan model persamaan struktural. Sebuah survei cross-sectional terhadap 409 guru mengindikasikan adanya peningkatan tingkat penerimaan dan literasi AI. Literasi AI secara kuat memprediksi penerimaan dan sebaliknya, menunjukkan adanya hubungan dua arah antara kedua variabel ini. Faktor demografis memberikan pengaruh yang minimal, sedangkan frekuensi penggunaan AI menunjukkan korelasi yang moderat antara kedua variabel tersebut. Model persamaan struktural mengungkapkan bahwa pengaruh sosial, kondisi yang memfasilitasi, dan perkembangan kompetensi AI secara signifikan mempengaruhi niat perilaku dan kesadaran etis guru. Temuan ini menggarisbawahi perlunya program pengembangan profesional yang komprehensif dan berbasis pengalaman yang mendorong keterlibatan yang mendalam, reflektif, dan etis dengan teknologi AI. Studi ini mengadvokasi pendekatan sistemik dan responsif secara budaya terhadap integrasi AI dalam pendidikan dasar, menyelaraskan pelatihan, infrastruktur, budaya kolaboratif, dan dukungan pribadi untuk mempersiapkan guru dalam pemanfaatan AI yang efektif dan bertanggung jawab.Kata kunci: kecerdasan buatan, literasi AI, UTAUT, penerimaan guru, pendidikan dasar.